2016
DOI: 10.1186/s12870-016-0893-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome responses of an ungrafted Phytophthora root rot tolerant avocado (Persea americana) rootstock to flooding and Phytophthora cinnamomi

Abstract: BackgroundAvocado (Persea americana Mill.) is a commercially important fruit crop worldwide. A major limitation to production is the oomycete Phytophthora cinnamomi, which causes root rot leading to branch-dieback and tree death. The decline of orchards infected with P. cinnamomi occurs much faster when exposed to flooding, even if flooding is only transient. Flooding is a multifactorial stress compromised of several individual stresses, making breeding and selection for tolerant varieties challenging. With mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 45 publications
1
55
0
2
Order By: Relevance
“…In addition to causing substantial economic losses in agriculture, forestry and horticulture, the inadvertent introduction of P. cinnamomi has had disastrous consequences for natural ecosystems and biodiversity. Prime examples include the impact of P. cinnamomi on chestnut and holm oak forests in Europe (Serrazina et al, 2015;Sghaier-Hammami et al, 2013), on avocado and macadamia worldwide (Akinsanmi et al, 2017;Reeksting et al, 2016) and on natural vegetation in south-east and south-west Australia (Cahill et al, 2008;Jung et al, 2013) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to causing substantial economic losses in agriculture, forestry and horticulture, the inadvertent introduction of P. cinnamomi has had disastrous consequences for natural ecosystems and biodiversity. Prime examples include the impact of P. cinnamomi on chestnut and holm oak forests in Europe (Serrazina et al, 2015;Sghaier-Hammami et al, 2013), on avocado and macadamia worldwide (Akinsanmi et al, 2017;Reeksting et al, 2016) and on natural vegetation in south-east and south-west Australia (Cahill et al, 2008;Jung et al, 2013) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…These unannotated data have been assembled into about 4000 contigs. At the time of writing, there were two published analyses of P. cinnamomi transcriptomes available (Meyer et al, 2016;Reitmann et al, 2016). The first reports data from Eucalyptus nitens, 5 days after inoculation with P. cinnamomi; the second reports data from a library of cysts and germinated cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Phytophthora species [95,101] our data permitted the identification of early induced genes such as TIPTOP, a P. palmivora-responsive root tip promoter. An exciting future perspective is its exploitation for induced early resistance against Phytophthora root infections.…”
Section: P Palmivora Triggers Expression Of Danger-associated Molecumentioning
confidence: 92%
“…MIPs have a main role in water and solute transport and aid in homeostasis during plant stress responses (Afzal et al, 2016). Recently, transcriptome data provided important clues about the involvement of MIPs in host-pathogen interactions (Galindo-Gonzàlez and Deyholos, 2016; Reeksting et al, 2016; Guo et al, 2017). Although there has been no study on PMIPs, in the present study, we identified and characterized a total of 126 MIP homologues from the genomes of six Phytophthora species, which cause severe economic losses because of devastating effects on numerous agriculturally and ornamentally important plants (Tyler et al, 2006; Haas et al, 2009; Lamour et al, 2012; Thines, 2014; Fawke et al, 2015; Derevnina et al, 2016; Wang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%